The effect of influenza and pneumococcal vaccination in the elderly on health service utilisation and costs: a claims data-based cohort study - Josephine Storch; Carolin Fleischmann-Struzek; Norman Rose; Thomas Lehmann; Anna Mikolajetz; Srikanth Maddela; Mathias W. Pletz; Christina Forstner; Ole Wichmann; Julia Neufeind; Monique Vogel; Konrad Reinhart; et al. (The European Journal of Health Economics, 2021)
Background: To date, cost-effectiveness of influenza and pneumococcal vaccinations was assumed in several health economic modelling studies, but confirmation by real-world data is sparse. The aim of this study is to assess the effects on health care utilisation and costs in the elderly using real-world data on both, outpatient and inpatient care. Methods Retrospective community-based cohort study with 138,877 individuals aged0.167em≥0.167em60~years, insured in a large health insurance fund in Thuringia (Germany). We assessed health care utilisation and costs due to influenza- or pneumococcal-associated diseases, respiratory infections, and sepsis in 2015 and 2016. Individuals were classified into four groups according to their vaccination status from 2008 to 2016 (none, both, or either only influenza or pneumococcal vaccination). Inverse probability weighting based on 236 pre-treatment covariates was used to adjust for potential indication and healthy vaccinee bias. Results Influenza vaccination appeared as cost-saving in 2016, with lower disease-related health care costs of - exteuro178.87 [95% CI - exteuro240.03;- exteuro117.17] per individual (2015: - exteuro50.02 [95% CI - exteuro115.48; exteuro15.44]). Cost-savings mainly resulted from hospital inpatient care, whereas higher costs occurred for outpatient care. Overall cost savings of pneumococcal vaccination were not statistically significant in both years, but disease-related outpatient care costs were lower in pneumococci-vaccinated individuals in 2015 [- exteuro9.43; 95% CI - exteuro17.56;- exteuro1.30] and 2016 [- exteuro12.93; 95% CI - exteuro25.37;- exteuro0.48]. Although we used complex adjustment, residual bias cannot be completely ruled out. Conclusion Influenza and pneumococcal vaccination in the elderly can be cost-saving in selective seasons and health care divisions. As cost effects vary, interpretation of findings is partly challenging.
Keywords: 610; Claims data; Real-world data; Influenza vaccination; Pneumococcal vaccination; Elderly; Cost; Health care utilisation